Determinants of banking consumers' engagement in post service failure positive word-of-mouth: Examining mediating mechanisms. Issue 2 (6th March 2019) - Harun, Ahasan; Rokonuzzaman, Md; Prybutok, Gayle; Prybutok, Victor R.
Abstract : Purpose: The purpose of this paper is to develop and examine a theoretical framework that evaluates the effects of banking consumers' justice perception on their post-complaint mindsets. It also aims to help business strategists to customize service failure management activities to achieve a competitive advantage. Design/methodology/approach: To examine the proposed framework using partial least square structural equation modeling, the authors collected data through a survey. The authors also evaluated the proposed framework through multi-group analysis and importance-performance map analysis (IPMA). Findings: Results show that recovery disconfirmation mediates the relationship between banking consumers' perception of justice and recovery satisfaction. Moreover, after a service failure, brand equity and loyalty mediate the relationship between recovery satisfaction and positive word-of-mouth behavior. IPMA analysis at the construct level shows that fostering the perception of recovery satisfaction is crucial for creating a positive post-failure impression in the mind of the banking consumer. Practical implications: For banking practitioners, the findings of this research provide a strategic blueprint for managing service failure by developing relationships with consumers, thus creating an opportunity to gain competitive advantage. Originality/value: Anchored in the theoretical framework of justice theory (Adams, 1963), expectation disconfirmation theory (Oliver, 1977 ) and social exchange theory (Kelley and Thibaut, 1978 ), the research adds to the literature by providing a critical evaluation of how to influence banking consumers' post-complaint behavior from a more systematic perspective.